2014
DOI: 10.1002/2014gl059874
|View full text |Cite
|
Sign up to set email alerts
|

Excursions in the 14C record at A.D. 774–775 in tree rings from Russia and America

Abstract: The calibration of radiocarbon dates by means of a master calibration curve has been invaluable to Earth, environmental and archeological sciences, but the fundamental reason for calibration is that atmospheric radiocarbon content varies because of changes in upper atmosphere production and global carbon cycling. Improved instrumentation has contributed to high-resolution (interannual) radiocarbon activity measurements, which have revealed sudden and anomalous activity shifts previously not observed at the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
114
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(125 citation statements)
references
References 43 publications
11
114
0
Order By: Relevance
“…The strongest peak of Δ 14 C, corresponding to the event of AD 775 (called henceforth M12), and another peak in AD 993/4 were measured by Miyake (Miyake et al 2012(Miyake et al , 2013) using 14 C in annually resolved Japanese cedar tree-ring sequences, and M12 has been confirmed by several studies (Usoskin et al 2013;Jull et al 2014;Güttler et al 2015;Rakowski et al 2015;Büntgen et al 2016) including three that showed peaks with slightly different starting times. Data from high-latitude Siberian and Altai (Jull et al 2014;Büntgen et al 2016) record the AD 775 peak but show a Δ 14 C rise beginning one year earlier, and Δ 14 C data in New Zealand kauri (Güttler et al 2015) indicate a peak delayed by half a year.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…The strongest peak of Δ 14 C, corresponding to the event of AD 775 (called henceforth M12), and another peak in AD 993/4 were measured by Miyake (Miyake et al 2012(Miyake et al , 2013) using 14 C in annually resolved Japanese cedar tree-ring sequences, and M12 has been confirmed by several studies (Usoskin et al 2013;Jull et al 2014;Güttler et al 2015;Rakowski et al 2015;Büntgen et al 2016) including three that showed peaks with slightly different starting times. Data from high-latitude Siberian and Altai (Jull et al 2014;Büntgen et al 2016) record the AD 775 peak but show a Δ 14 C rise beginning one year earlier, and Δ 14 C data in New Zealand kauri (Güttler et al 2015) indicate a peak delayed by half a year.…”
Section: Introductionmentioning
confidence: 71%
“…The Carrington Event of 1859 involved major magnetic storms on August 28-29 and September 2-3, with auroras visible at geomagnetic latitudes as low as 25°and 18°, respectively (Green and Boardsen 2006), suggesting that two closely spaced CMEs interacted strongly with the geomagnetic field. As noted by Jull et al (2014), there is no evidence for this event in the annual 14 C record, which at first sight appears to Solar Activity and Δ 14 C Peaks 1153 https://www.cambridge.org/core/terms. https://doi.org/10.1017/RDC.2017.59 challenge the hypothesis outlined above, but we have no information on the intensity, spectrum, and duration of the SEP event and the conditions for efficient particle acceleration leading to a very hard energy spectrum may not have been met (Li et al 2006).…”
Section: Solar Proton Events and Coronal Mass Ejectionsmentioning
confidence: 92%
See 3 more Smart Citations